Penyuluhan Kesehatan Penyakit Diabetes Melitus di Desa Simpang Empat Sungai Baru Tanah Laut - Tio Widia Astuti Marpaung; Dwi Wulan Apriani; Ahmad Nurwanto; Ika Pratiwi; M Aisy Akbar Firdaus; Adelia Sisilia; Citra Ukhti Kamila; Luna Septiana; Amelia (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
Diabetes mellitus is a non-communicable disease with a continuously increasing prevalence and remains a major public health concern. Limited community knowledge regarding risk factors, symptoms, prevention, and management of diabetes mellitus may increase the risk of complications. This community service program aimed to improve public knowledge through health education in Simpang Empat Sungai Baru Village, Tanah Laut Regency. The activity was conducted on May 12, 2026, involving 73 participants. Educational interventions were delivered through lectures, interactive discussions, and question-and-answer sessions, while evaluation was carried out using pre-test and post-test questionnaires. The results showed an improvement in participants’ knowledge following the intervention. A total of 81% of participants achieved a good level of knowledge, while 12% and 7% were categorized as having moderate and poor knowledge, respectively. Participants also demonstrated high enthusiasm and active participation throughout the program. These findings indicate that health education is effective in enhancing community knowledge of diabetes mellitus and can support disease prevention efforts through the adoption of sustainable healthy lifestyle behaviors.